Presence of Staphylococcus aureus and Shiga Toxigenic Escherichia coli O157:H7 in Raw Meat in Ağrı, Turkey - Naim Deniz Ayaz (International Journal of Enteric Pathogens, 2016)
Background: Staphylococcus aureus and Shiga toxin producing Escherichia coli O157:H7 (EHEC) are significant foodborne pathogens worldwide. While S. aureus can cause mild superficial skin infections or life-threatening bacteremia and endocarditis, as well as toxininduced cases such as toxic shock syndrome; E. coli O157:H7 can cause symptoms from mild diarrhea to severe hemorrhagic colitis (HC), hemolytic uremic syndrome (HUS), thrombotic thrombocytopenic purpura (TTP). Objectives: The objectives of this study were to find out the prevalence and seasonal distribution of S. aureus in 214 frozen raw meat (turkey, chicken and beef) and the prevalence of E. coli O157:H7 in 70 raw beef with the characterization of the E. coli O157:H7 isolate by multiplex polymerase chain reaction (PCR). Materials and Methods: For the detection of S. aureus, a total of 214 frozen raw meat samples including 74 turkey meat, 70 chicken meat and 70 beef cuts (approximately 2 × 3 cm cubic parts); and for the detection of E. coli O157:H7, a total of 70 frozen raw beef samples that all were produced from national companies and consumed in Ağrı, Turkey were analyzed. Results: Out of 214 meat samples, 25.7 % (18/70) of the beef, 11.4 % (8/74) of the chicken meat, and 5.4 % (4/70) of the turkey meat samples were contaminated with S. aureus. Out of 70 frozen raw beef samples, only 1 (1.4%) was identified as both Shiga toxin 1 and 2producing E. coli O157:H7 by the detection of stx1, stx2, eaeA, hly, and fliCh7 according to multiplex PCR analysis. Conclusion: Our findings demonstrate that occurrence frequency of S. aureus was higher in frozen raw beef than in raw chicken and turkey meat samples. Although the prevalence of E. coli O157:H7 was low in beef, the presence of virulence genes, especially toxin genesrema in a significant public health concern.